A 6.4 Gbit/s Embedded Compression Codec for Memory-Efficient Applications on Advanced-HD Specification - Tsai, Tsung-Han; Lee, Yu-Hsuan (IEEE transactions on circuits and systems for video technology, 2010)
The embedded compression (EC) technique is applied to reduce the memory bandwidth and capacity in a display system. In this paper, the high-speed EC algorithm is proposed for advanced-HD specification. It mainly comprises three features: 1) the associated geometric-based probability model is developed to construct context-modeling mechanism without context-table; 2) develop content-adaptive Golomb-Rice code and geometric-based binary code as the entropy coding with minor order of context; and 3) provide the rate control mechanism to guarantee the saving ratio of memory bandwidth and capacity. With competitive coding efficiency, the computation-efficiency of the proposed EC algorithm is about 44% and 40% of FELICS and JPEG-LS. The proposed very-large-scale integration architecture of entire codec is implemented in TSMC 0.18- 1P6M CMOS technology. Based on pixel-based parallelism and segment-based parallelism techniques, the encoding/decoding capability reaches Quad Full-high definition (QFHD) (3840 × 2160) at 30 Hz. The maximum throughput is as high as 6.4 Gbit/s. Furthermore, with multi-level parallelism, the performance can be extended to QHD (2560 × 1440) at 120 Hz and QFHD at 120 Hz for the double frame rate technique.